Evaluation and Management of Skeletal Health in Celiac Disease: Position Statement - Mona A Fouda; Aliya A Khan; Muhammad Sultan; Lorena P Rios; Karen McAssey; David Armstrong (Canadian Journal of Gastroenterology)
OBJECTIVE: To review the evaluation and management of skeletal health in patients with celiac disease (CD), and to make recommendations on screening, diagnosis, treatment and follow-up of low bone mineral density (BMD) in CD patients.